Medical and social aspects of health security in the formation of public health - O. Sh. Oynotkinova; V. N. Larina (Здоровье мегаполиса)
Introduction. Monitoring of the health status of the population as a whole, assessment and analysis of the leading determinants of health, including genetic, behavioral, anthropogenic, biophysiological factors, represent one of the global functions of public health, focused on health protection and provision of medical services. To date, health disorders are primarily related to lifestyle and are always a collection of individual personalized health data. Unhealthy diet and low physical activity are risk factors for the development of a number of chronic non-communicable diseases, primarily cardiovascular, metabolic, in particular type 2 diabetes mellitus and some types of cancer. These risk factors lead to early disability, a decrease in the quality and life expectancy of people, disability, as well as the health budget and the economy. So, if on average only 3 % of the health budget is spent on disease prevention programs, then about 7 % of the budget in the EU countries is spent on the treatment of obesity and turns into 2.8 % of world GDP. In this regard, the implementation of early preventive measures is characterized by favorable and positive results.Purpose. Analyzes the role of unhealthy diet and low physical activity as key risk factors for cardiovascular and metabolic diseases, especially in the population of patients with type 2 diabetes mellitus.Methods and materials. The characteristics of the presented studies included in the article cover international experience and analysis of the pilot study conducted on a population sample of patients with type 2 diabetes mellitus. To assess the economic costs associated with unhealthy diet and low physical activity, a general approach was used based on the analysis of individual diseases, in particular, type 2 diabetes mellitus, using population attributive fractions, regression method.Results. Based on the data obtained, it follows that patients with an unhealthy diet and low physical activity, burdened with overweight or obesity, have a high five-year risk of developing new cases of type 2 diabetes and cardiovascular complications. This includes early disability and the economic costs of providing medical care. Using the example of a number of European countries and its own results, this study is focused on assessing the economic damage that is associated with unhealthy diet and low physical activity among the population, regardless of the region of residence and the metropolis.